"Eco‐Friendly" Epimerization of Lutein to 3′‐Epilutein Under Solvent‐Free Mechanochemical Conditions by Using a Strongly Acidic Cation‐Exchange Resin. Issue 24 (25th June 2018) - Sánchez‐Chávez, Anahí C.; Mendoza‐Figueroa, Humberto L.; Oliveros‐Cruz, Saray; Torres‐Cardona, Mario D.; Luján‐Montelongo, J. Armando; Polindara‐García, Luis A.
Abstract : Carotenoids represent a wide group of biologically active molecules found in nature with important applications in the food, cosmetics, and pharmaceutical industries. For example, lutein and its isomers meso ‐ and trans ‐zeaxanthin are globally the best‐selling carotenoids in terms of market value owing to their benefits to eye health. Here, the development of a solvent‐free mechanochemical epimerization protocol to convert naturally occurring lutein into 3′‐epilutein‐enriched mixtures (up to dr 37:63 lutein/3′‐epilutein) by using a strongly acidic cation‐exchange resin as an "eco‐friendly" catalyst is reported. Abstract : A solvent‐free mechanochemical epimerization protocol to convert a naturally occurring lutein‐containing extract into 3′‐epilutein‐enriched mixtures by using a strongly acidic cation‐exchange resin as "eco‐friendly" catalyst has been developed. This emerging methodology shows clear advantages over known Brønsted acidic epimerization methods in terms of time and reduction of harmful waste products.